Prevalência de morbidades clínicas em mulheres na pós menopausa atendidas na unidade de referência materno infantil em Belém-Pa - MIRANDA, Diane da Costa (2023)
Introduction – Climateric is a stage of woman’s life characterized by a progressive reduction in the production of estrogens, bringing physical, emotional and social impacts. According to IBGE, in Brazil there are 97,3 million women, 26% are at the age of occurrence of the climateric. The clinical morbidity in this period further affect the life’s quality of this portion of the population, so understand theses diseases is central in the approach of these women. Objective – Verify the prevalence of clinical morbidity in postmenopausal women attended at a Pediatric and Maternal referral Unit in Belém-PA. A cross-section study of postmenopausal women attended in a climateric ambulatory at a Pediatric and Maternal referral Unit in Belém-PA. We used a pre-structured questionnaire, based on data from anamnesis and physical examination, as well as medical records. Results – Were interviewed 74 women, most were aged between 50-59 years, was mulatto and had low scholarity. The most prevalent diseases were, by frequency order, Dyslipidemia, Metabolic Syndrome, Hypertension, Obesity, Diabetes and Hypothyroidism. Dylipidemia was associated with low scholarity and smoking habit. Metabolic Syndrome was associated whit high scholarity. Hypertension was related whit high scholarity and single status. Obesity was also associated whit low scholarity. We don’t find association between Diabetes and the factors investigated. Finally, Hypothyroidism was associated whit black and yellow race. Conclusion - Dylipidemia was the most prevalent disease. Most diseases have modifiable risk factors, so is important to encourage the health promotion and prevention of these injuries.